1997
DOI: 10.7547/87507315-87-2-66
|View full text |Cite
|
Sign up to set email alerts
|

Nonossifying fibroma. Four cases and review of the literature

Abstract: Nonossifying fibroma is a benign, lytic lesion that occurs in young children and adolescents. Radiographically, the lesion is multilocular and sharply demarcated. It often occurs at the metaphyseal region of long bones of the lower extremity and is usually eccentrically located. Four cases of nonossifying fibroma occurring during the past 7 years are presented with a review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 1 publication
1
15
0
Order By: Relevance
“…Although uncommon, we agree with Glockenberg et al who described in their paper that the age range for this condition is 3 to 42 [1]. Most literature state that there is a higher male predominance to females; and this was estimated to be 2:1 [1,2]. The condition most commonly affects the metaphyseal region of bone [1] , namely the distal femur followed by the proximal tibia [1,3].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Although uncommon, we agree with Glockenberg et al who described in their paper that the age range for this condition is 3 to 42 [1]. Most literature state that there is a higher male predominance to females; and this was estimated to be 2:1 [1,2]. The condition most commonly affects the metaphyseal region of bone [1] , namely the distal femur followed by the proximal tibia [1,3].…”
Section: Discussionsupporting
confidence: 89%
“…It is well recognized that non-ossifying fibroma is a benign tumor occurring mainly in childhood and adolescence [1] . Although uncommon, we agree with Glockenberg et al who described in their paper that the age range for this condition is 3 to 42 [1]. Most literature state that there is a higher male predominance to females; and this was estimated to be 2:1 [1,2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibrous cortical defects are common; non-ossifying fibromas are less frequently seen; and patients with Jaffe-Campanacci syndrome are only very rarely encountered [1-3, 8, 9, 14, 20, 27, 32, 34, 41, 45, 56, 61]. The lesions are principally metaphyseal in location and the distal femur, proximal tibia, distal tibia, proximal humerus, fibula and radius are the most common sites [2,3,7,9,13,14,20,41,51,56,61]. The fibrous cortical defect is usually asymptomatic and is only discovered by an X-ray being performed for another problem.…”
Section: Clinical Presentationsmentioning
confidence: 98%
“…The FCD and the NOF are the most common benign lesions of the skeletal system [1,8], arising most frequently in the metaphyseal region of the distal femur, proximal and distal tibia and fibula in children and adolescents [9]. Radiographic studies in the orthopedic literature have shown that 33 % of otherwise normal children have one or more small fibrous cortical defects [1].…”
Section: Introductionmentioning
confidence: 99%